Ukuran Dewan Komisaris, Konsentrasi Kepemilikan, dan Leverage Perusahaan - Setiawan, Rahmat; Widharta, Anggita Ayu (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This purpose of this study is to examine the effect of board size, and the moderating effect of ownership concentration on corporate leverage in non-financial companies in Indonesia listed on the Indonesia Stock Exchange in 2014-2016. This study uses multiple regression analysis and MRA (Moderated Regression Analysis) to test the research hypothesis. The results showed that board size had a significant negative effect on leverage. In addition, it can also be seen that the moderating effect of ownership concentration weakens the negative effect of board size on company leverage.